Health belief model of parents’ COVID-19 vaccination intentions for children: perceived benefits and barriers in Indonesia - Handayani, Eka Wuri; Perwitasari, Dyah Aryani; Purba, Fredrick Dermawan (Frontiers in Public Health, 2025)
IntroductionThe uptake of vaccines against COVID-19 remains low. Some barriers to childhood vaccination uptake persist, such as parents’ assumption that children are at lower risk of severe COVID-19 and tend to be asymptomatic carriers. This study aims to develop guidance for in-depth interviews for a future qualitative study based on a cross-sectional quantitative study of parents with school-age children.MethodsThis study adopted a cross-sectional design. The study population comprised parents of 6–11-year-old children in the Centra Java province who had received the COVID-19 vaccine or not. The data were collected from August 2023 by filling in an online questionnaire. The sample size was calculated using formulation in OpenEpi for 95% confidence levels, with a statistical power of 80%.ResultsOur study finds that perceived benefit and perceived barriers are the two domains that most significantly influenced the parents’ intention to vaccinate their children. In our study, there was no significant association between parent gender and the intention to vaccinate their children. Our study shows that parents’ acceptance of vaccinating their children is high. We emphasized questions related to benefits and barriers in the interview. The questions on perceived benefits explored the advantages of COVID-19 vaccination. The content on perceived barriers examined the concerns of parents, the information influencing their decision to vaccinate their child, the procedure vaccination and the effect after vaccination.DiscussionThe significant association between parents’ intention to vaccinate their children and the perceived benefits and perceived barriers to vaccination generated guidance for in-depth interviews in the qualitative study. The health belief model should be further explored in Indonesia because of the potential external factors that may influence parents’ intention to vaccinate their children.